The burden of physical disability among patients with newly detected leprosy in Yunnan, China, 1990-2020: A population-based, cross-sectional survey - Xiaohua Chen; Tie-Jun Shui (Public Library of Science (PLoS), 2022)
Background Physical disability is the main complication of leprosy. Although understanding the leprosy rate, prevalence, spatiotemporal distribution, and physical nerve characteristic trends is crucial for the implementation of leprosy control programs and identification of remaining challenges, these data are still unclear. We assessed physical disability trends among newly detected leprosy cases over the past 31 years in 129 counties and territories in Yunnan, China. Methodology/Principal findings We analyzed the data of newly detected leprosy cases from the Leprosy Management Information System in Yunnan, China, from 1990-2020. All available data related to physical disability were analyzed, including demographic characteristics (sex, age, ethnicity, education level); clinical characteristics (diagnosis duration, detection mode, contact history, leprosy reaction, skin lesions, nerve lesions, disability classification); World Health Organization (WHO) leprosy physical disability indicators; and nerve and eyes, hands and feet (EHF) involvement. A total of 10758 newly diagnosed leprosy cases were identified, and 7328 (65.60%), 1179 (10.55%) and 2251 (20.15%) were associated with grade 0, 1, and 2 disability (G0D, G1D, and G2D), respectively. Male sex, older age, Han ethnicity, urban employment, a longer diagnosis duration, a contact history, greater nerve involvement, and tuberculoid-related forms of leprosy were associated with increased prevalence rates of physical disability. The rates of physical disability in newly detected leprosy cases per 1 million population decreased from 5.41, 2.83, and 8.24 in 1990 to 0.29, 0.25, and 0.54 per 1 million population in 2020, with decreases of 94.64%, 91.17%, and 93.44% in G2D, G1D and total physical disability (G1D + G2D) rates, respectively. In the same period, the proportions of G2D, G1D and total physical disability decreased from 28.02%, 14.65%, and 42.67% in 1990 to 10.08%, 11.76%, and 21.85% in 2020, with decreases of 64.03%, 19.73%, and 48.79%, respectively. Nerve thickening was more common than nerve tenderness, and claw hand, plantar insensitivity, and lagophthalmos were the most frequently reported EHF-related disabilities. Conclusions Despite general progress in reducing the prevalence of leprosy-related physical disability, the proportion of physical disability among leprosy disease remains high, especially in specific counties. This implies that leprosy cases are being detected at a later stage and that transmission in the community still exists. Further efforts focusing on early detection are crucial for leprosy control and the elimination of the disease burden. Author summary Leprosy, caused by Mycobacterium leprae (M. leprae), is a potentially disabling infectious disease. An understanding of the leprosy rate, prevalence, spatiotemporal distribution, and nerve characteristic trends are crucial for the implementation of leprosy control programs the identification of remaining challenges. The physical disability trends among newly detected leprosy cases were assessed over a 31-year period in Yunnan, a leprosy-endemic region in China. A total of 10758 newly diagnosed leprosy cases were reported, and 10.55% (1179) and 20.15% (2251) of patients were diagnosed with grade 1 (G1D) and grade 2 disability (G2D), respectively. Male sex, older age, Han ethnicity, urban employment, a longer diagnosis duration, a contact history, greater nerve involvement, and tuberculoid-related forms of leprosy were associated with increased prevalence rates of physical disability. Despite general progress in reducing the prevalence of leprosy-related physical disability, the proportion of those experiencing physical disability due to leprosy is still high. This implies that leprosy cases are being detected at a later stage and that transmission in the community remains. Further efforts focusing on early detection are crucial for leprosy control and the elimination of the disease burden.